Ethnobotany: From the Traditional to Ethnopharmacology - Book Review - Reza, Ahmad Reza Maulana; Meri, Merinah; Ria, Ria Puspitaningrum (Ethnobotany Research and Applications, 2025)
As highlighted in Ethnobotany: From the Traditional to Ethnopharmacology, edited by José L. Martinez, Alfred Maroyi, and Marcelo L. Wagner (2023), this book presents the latest research on the potential of plants commonly used in traditional medicine and their pharmacological applications. The need for new and alternative treatments arises from the inefficacy of some current therapies for various diseases. This compilation provides valuable insights for researchers aiming to develop novel medications.